2019
DOI: 10.1080/17430437.2019.1669322
|View full text |Cite
|
Sign up to set email alerts
|

‘I was excited to train, so I didn’t have problems with the coach’: dual career athletes’ experiences of (dis)empowering motivational climates

Abstract: In Copyright http://rightsstatements.org/page/InC/1.0/?language=en 'I was excited to train, so I didn't have problems with the coach' : dual career athletes' experiences of (dis)empowering motivational climates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Our findings are in line with previous DC studies that found that, when facing challenges in DC, student-athletes will prioritise sports (Saarinen et al, 2020;Stambulova et al, 2015). Furthermore, when the student-athletes in this study faced challenges in the sports domain, they reported a decrease in motivation toward the school.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with previous DC studies that found that, when facing challenges in DC, student-athletes will prioritise sports (Saarinen et al, 2020;Stambulova et al, 2015). Furthermore, when the student-athletes in this study faced challenges in the sports domain, they reported a decrease in motivation toward the school.…”
Section: Discussionsupporting
confidence: 92%
“…Since the espoused values stated by the gatekeepers contradicted the basic assumptions, the present study of the sports academy complements the studies on the rhetorical support of DC and the instrumental role of the education in the sporting environments by Saarinen et al (2020) and Thomsen and Nørgaard (2018). According to the Schein (1990), culture is taught to new members by the leading figures and role models.…”
Section: Discussionmentioning
confidence: 83%
“…Youth athletes, especially in the Nordic cultures, are increasingly expected to sustain their athletic and educational careers so as not to restrict their life opportunities (Ryba et al, 2016b). However, committed participation in both domains is highly demanding, and success in one domain often comes at the expense of the other (e.g., Cosh & Tully, 2014;Elliott et al, 2018;Ryba et al, 2015;Saarinen et al, 2020), and sports is often prioritized over school (Cosh & Tully, 2014;Nikander et al, 2020). Since the literature indicates that challenges confronting dualcareer athletes may be gendered, the present study aimed to examine whether gender plays a role in the simultaneous development of sports-and school-related values.…”
Section: Discussionmentioning
confidence: 99%
“…The central question is how athletes' motivation for both is maintained throughout their upper secondary school years. For example, the pressure to combine an academic and sports career may render adolescent athletes vulnerable to stress and burnout (Sorkkila et al, 2020) and even loss of motivation in the area of mastery they once experienced as inspiring (Baron-Thiene & Alfermann, 2015;Saarinen et al, 2020).…”
Section: Dual Careermentioning
confidence: 99%
See 1 more Smart Citation